The dynamics of Black Sea subregionalism - Manoli, Panagiota (Ashgate Pub., 2012)
Conflict and cooperation are two dynamics that have shaped the political economy and international relations around the Black Sea since the early nineties. This title examines the process of institutionalized subregional cooperation and casts light on the factors influencing the reconfiguration of subregional structures in the region.